Memory consolidation in sleep disorders. (October 2017) - Cellini, Nicola
Summary: In recent years sleep-related memory consolidation has become a central topic in the sleep research field. Several studies have shown that in healthy individuals sleep promotes memory consolidation. Notwithstanding this, the consequences of sleep disorders on offline memory consolidation remain poorly investigated. Research studies indicate that patients with insomnia, obstructive sleep apnea, and narcolepsy often exhibit sleep-related impairment in the consolidation of declarative and procedural information. On the other hand, patients with parasomnias, such as sleep-walking, night terrors and rapid eye movement (REM) behavior disorder, do not present any memory impairment. These studies suggest that only sleep disorders characterized by increased post-learning arousal and disrupted sleep architecture seem to be associated with offline memory consolidation issues. Such impairments, arising already in childhood, may potentially affect the development and maintenance of an individual's cognitive abilities, reducing their quality of life and increasing the risk of accidents. However, promising findings suggest that successfully treating sleep symptoms can result in the restoration of memory functions and marked reduction of direct and indirect societal costs of sleep disorders.